Mapping the Neuroanatomy of ABHD16A, ABHD12, and Lysophosphatidylserines Provides New Insights into the Pathophysiology of the Human Neurological Disorder PHARC - Singh, Shubham; Joshi, Alaumy; Kamat, Siddhesh S (Biochemistry (Easton), 2020)
Lysophosphatidylserine (lyso-PS), a lysophospholipid derived from phosphatidylserine (PS), has emerged as a potent signaling lipid in mammalian physiology. In vivo, the metabolic serine hydrolases ABHD16A and ABHD12 are major lipases that biosynthesize and degrade lyso-PS, respectively. Of biomedical relevance, deleterious mutations to ABHD12 cause accumulation of lyso-PS in the brain, and this deregulated lyso-PS metabolism leads to the human genetic neurological disorder PHARC (polyneuropathy, hearing loss, ataxia, retinitis pigmentosa, and cataract). While the roles of ABHD16A and ABHD12 in lyso-PS metabolism in the mammalian brain are well established, the anatomical and (sub)cellular localizations of both lipases and the functional cross-talk between them with respect to regulating lyso-PS lipids remain under investigated. Here, using subcellular organelle fractionation, biochemical assays, and immunofluorescence-based high-resolution microscopy, we show that the PS lipase ABHD16A is an endoplasmic reticulum-localized enzyme, an organelle intricately regulating cellular PS levels. In addition, leveraging immunohistochemical analysis using genetic ABHD16A and ABHD12 knockout mice as important controls, we map the anatomical distribution of both of these lipases in tandem in the murine brain and show for the first time the distinct localization of these lipases to different regions and cells of the cerebellum. We complement the aforementioned immunohistochemical studies by quantitatively measuring lyso-PS concentrations in various brain regions using mass spectrometry and find that the cerebellar lyso-PS levels are most affected by deletion of ABHD16A (decreased) or ABHD12 (increased). Taken together, our studies provide new insights into lyso-PS signaling in the cerebellum, the most atrophic brain region in human PHARC subjects.